Mapping the relationship among quality management practices, organizational learning, organizational culture, and organizational performance in higher education: a proposed framework - Mohammed, Ahmad Hani; Taib, Che Azlan; S.R. Nadarajan, Santhirasegaran (Scientific Research Publishing Inc., 2015)
The challenges in higher education and global competition encouraged performance excellence and the pursuit towards providing educational services characterized by high quality. To ensure performance excellence, quality management practices are considered as one of the variables that affect the organizational performance. On the other hand, organizational learning is a method that facilitates the process of improving the organizational performance. The results of organizational performance vary according to environmental conditions, especially an organizational culture that is one of the important indicators that are characterized by organizations. This encourages choosing the organizational culture as a moderating variable. However, this paper highlights organizational performance through a proposed conceptual framework to be considered in higher education institutes.